Efektifitas Peran Pengadilan Agama Terhadap Pelaksanaan Batas Usia Perkawinan Sebagai Upaya Penurunan Angka Pernikahan Dini: Studi di Pengadilan Agama Sukoharjo Pada Tahun 2024 - Fisterina Wardani; Achmad Denny Maulana; Kinanti Citra Prasasti; Dinar Kristina Kusumawati; Amelia Dwi Callista; Josef Purwadi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research is entitled "Effectiveness of the Role of Religious Courts in the Implementation of Marriage Age Limits as an Effort to Reduce the Rate of Early Marriage (Study at the Sukoharjo Religious Court in 2024)" which is based on a phenomenon in society related to the rise of teenagers having relationships like husband and wife. to pregnancy out of wedlock at an age that has not yet reached the minimum age limit for marriage. Islamic law does not provide clear boundaries for marriage, it only determines the measure of a person's maturity when they reach puberty. Islamic jurisprudence scholars agree in determining taklif, namely when semen comes out for men and menstruation for women, which is different from Law Number 1 of the Year. 1974 provides a clear age limit for someone to get married, namely 19 years for men and 16 years for women. Marriage dispensation is a grant of the right to a person to marry even though they have not yet reached the minimum marriageable age. Marriage dispensation is regulated in Article 7 paragraph (2) of Law Number 16 of 2019, an amendment to Law Number 1 of 1974 concerning Marriage. Marriage dispensation is an exception to Article 7 paragraph (1), namely that the age limit for marriage for men and women has reached 19 (nineteen) years. This type of research is field research or field research which can also be called qualitative research. Therefore, the author conducted this research at the Sukoharjo Religious Court, regarding data sources the author chose primary data sources, namely data from the court and secondary data sources, namely from several books as references. The data collection techniques used are observation, documentation and archive methods. The approach method used in this research is normative juridical, namely research that begins deductively with an analysis of the articles in the statutory regulations that regulate the above problems. Juridically, this means research that refers to existing literature studies or secondary data used. Meanwhile, normative means legal research which aims to obtain normative knowledge about the relationship between one regulation and another and its application in practice. The method used is a descriptive method by means of document analysis. In other terms it is also called content analysis or information analysis which focuses its activities on document research, analyzing regulations and legal decisions.